The influence of the type of anti-foaming admixture and superplasticizer on the properties of self-compacting mortar and concrete - Łazniewska-Piekarczyk, Beata; Szwabowski, Janusz (Journal of Civil Engineering and Management, 2012)
To prevent excessive air entrainment, superplasticizers (SPs) should not only be compatible with cement, but also should not create the air-entraining effect in mortar. In order to counteract excessive air entrainment, anti-foaming admixtures (AFAs) can be used to prevent the formation of air bubbles. This paper investigates the influence of the type, amount and time of introduction of AFAs on air-entrainment, rheological properties and workability loss of self-compacting mortar. The research results prove that AFAs decrease air-content in mortar. Mortar containing an AFA does not undergo segregation, as is the case with mortars of a similar degree of fluidity with no AFA and incorporating an SP only. Moreover, mortar with an AFA keeps initial consistency for longer in comparison to mortar with a SP only. The properties of hardened mortar mixes are also investigated. The research results show that AFAs do not have a significant influence on the compressive strength of mortar mixtures. The compressive strength of mortar mixtures incorporating an AFA is similar to mortar with a non-air-entraining SP. Moreover, AFAs increase significantly the flexural strength of mortar. In most cases, AFAs do not decrease the absorbability of mortar. Only two types of AFAs increase slightly the absorbability of mortar. In order to explain this phenomenon, a research was performed investigating the porosity structure according to the EN 480-11 (1999) and SEM analyses of two types of self-compacting concrete (SCC): one made of mortar with an AFA and the other without AFA. The freeze-proof resistance of SCC (made of the same mortar mixes) was also investigated according to PN-88/B-06250 (2003). The results show that the type of AFA and SP significantly influences porosity characteristics and frost-resistance of SCC.